(untitled) (Altre Modernità, 2022)
The work of Diamanda Galás (San Diego, 1955) constitutes a first historical case of total synthesis in vocal art, since it implies a compositional-performative competence that includes all styles of singing, learned and popular, and all existing phonatory techniques, even extreme and anomalous. According to a political conception of art, this technical-stylistic versatility is put at the service of the expression of trauma, of the evil inflicted and suffered by humanity. To this end, the voice gives a sound form both to the identity of the offender and to the identity of the victim, so that the unity of the vocal action represents the intrinsic moral ambivalence of man. Galás’s use of the voice demonstrates that the traumatic vocal material is not expressively neutralizable, reducible to an element of a purely formal combination. Galás’s work therefore serves as a paradigm for a general reflection on the aesthetics of trauma, where the function of antiphrasis is revealed to be structural: for the purposes of aesthetic transcendence, art cannot do without trauma.